The polysaccharides from pterospartum tridentatum (l.) Willk. Inflorescences and their contribution to in vitro macrophage nitric oxide production - Martins, Vitor Manuel Ramalheira (2018)
The decoctions of prickled broom (Pterospartum tridentatum (L.) Willk.) dried inflorescences have claimed beneficial properties for various health disorders1'2'3. These can be assigned to several constituents, among them, the polysacharides. In order to unveil the contribution of the polysacharides and their structural features to the modulation of the innate immune activity, the hot water extracts from P. tridentatum dried inflorescences were prepared and fractionated by ethanol precipitation and anion exchange chromatography. A fraction that mainly contained pectic polysaccharides and acetylated galactomannans was isolated.